2021
DOI: 10.1021/acsomega.1c02056
|View full text |Cite
|
Sign up to set email alerts
|

New Pregnane Glycosides Isolated from Caralluma hexagona Lavranos as Inhibitors of α-Glucosidase, Pancreatic Lipase, and Advanced Glycation End Products Formation

Abstract: Caralluma hexagona Lavranos (Family Asclepiadaceae) is an endemic herb in Yemen and Saudi Arabia, traditionally used to treat diabetes, abdominal pain, and stomach ulcers. Different extracts, fractions, and main constituents of C. hexagona were evaluated for their inhibitory activity against key enzymes in diabetes and hyperlipidemia, i.e., α-glucosidase and pancreatic lipase. In addition, the antioxidative effect and inhibition of advanced glycation end products (AGEs) were also assayed. Using a bioguided app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Consequently, HP20 resin was considered as the most suitable adsorbent for further enrichment of TFs in Kushui rose waste. It is widely reported that HP20 resin can be chosen to recover natural products from plant materials [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, HP20 resin was considered as the most suitable adsorbent for further enrichment of TFs in Kushui rose waste. It is widely reported that HP20 resin can be chosen to recover natural products from plant materials [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Legumes and cereals are able to reduce postprandial glucose levels by decreasing carbohydrate absorption due to their high complex carbohydrates and fiber contents [9]. Moreover, many medicinal plants are known for activity in diabetic complications, like green tea, Garcinia cambogia, Nigella sativa, Hibiscus sabdariffa, Caralluma fimbriata [10], C. tuberculata [11], and C. hexagona [12]. The spurge family, Euphorbiaceae, is a large flowering plant family with 300 genera and about 7500 species that has different traditional uses [13].…”
Section: Introductionmentioning
confidence: 99%
“…Flavone glycosides, pregnane glycosides, saponins, triterpenoids, and other flavonoids are important phytochemical constituents of C. fimbriata that have been studied against various pathological conditions and metabolic disorders. Pregnane glycosides are the secondary metabolites of C. fimbriata that are the steroidal compounds conjugated with sugar moiety [ 26 ]. They are related to altered lipid metabolism and inhibit the synthesis of fatty acids [ 18 , 27 ].…”
Section: C Fimbriata: An Edible Wild Medicinal Plantmentioning
confidence: 99%
“…Insulin resistance and related disorders such as obesity and type 2 diabetes mellitus are linked to a high dietary fat intake. Controlling postprandial hyperglycemia and fat absorption through inhibition of enzymes responsible for glycoside and lipid hydrolysis should help to reduce MS complications [ 26 ]. The hypoglycemic action of the pregnane glycoside is mainly attributed to the lowering of intestinal glucose absorption or stimulation of pancreatic insulin production [ 58 ].…”
Section: Therapeutical Potential Of C Fimbriata Ag...mentioning
confidence: 99%